(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
This study examines the relationship between digital literacy and communicative competence in English among 25 Uzbek undergraduate EFL learners, using a correlational research design. Digital literacy, including the ability to use digital tools for communication and information processing, was evaluated through practical tasks and self-assessment surveys. Communicative competence was assessed through role-play, group discussions, and writing tasks. The results revealed a strong and statistically significant positive correlation (r=0.957r = 0.957r=0.957, p<.001p < .001p<.001), showing that participants with higher digital literacy showed greater communicative competence. These findings highlight the synergistic relationship between digital literacy and language proficiency, emphasizing the importance of integrating digital literacy into English language classes. The study also emphasizes on the potential of integrating digital tools to combine language learning in real-world contexts, contributing to the development of technology-integrated pedagogical strategies.